Primary breast osteosarcoma: A diagnostic challenge - Krishnamurthy, Arvind (Indian J Nucl Med, 2015)
Extraskeletal osteosarcomas account for < 1% of the soft tissue sarcomas and are known to more often localize in soft tissues of the lower extremities. Primary osteosarcomas of the breast are extremely rare. A majority of the reported cases were in fact initially erroneously diagnosed and treated as primary breast carcinomas. We recently got to treat an interesting case of a primary breast osteosarcoma and discuss its evaluation and management with added emphasis on the incremental role of technetium 99-methylene diphosphonate (Tc-99m) bone scintigraphy in its clinical diagnosis. Tc-99m uptake can occasionally be seen in the delayed bone scintigraphy images of extra skeletal malignancies, but the uptakes are considered to be typically less intense than the uptakes noted in primary skeletal malignancies. Extraskeletal osteosarcomas are however the exceptions to this rule, the intense uptake in bone scintigraphy further aided in an accurate preoperative diagnosis and management of our patient.